Smoking and Skin Diseases: A Crucial Causal Link (Bangladesh Medical Journal, 2014)
Tobacco smoking is a serious and preventable health hazard that can cause or exacerbate a number of diseases and shorten life expectancy, but the role of smoking as an etiologic factor in the development of skin disease is largely unknown. Although epidemiological evidence is sparse, findings suggest that tobacco smoking is a contributing factor in systemic lupus erythematosus, psoriasis, palmoplantar pustulosis, cutaneous squamous cell carcinoma, hidradenitis suppurativa, and genital warts. In contrast, smoking may confer some protective effects and mitigate other skin diseases, notably pemphigus vulgaris, pyoderma gangrenosum, aphthous ulcers, and Behçet's disease. Various degenerative dermatologic conditions are also impacted by smoking, such as skin wrinkling and dysregulated wound healing, which can result in post-surgical complications and delayed or even arrested healing of chronic wounds. Most likely, alteration of inflammatory cell function and extracellular matrix turnover caused by smoking-induced oxidative stress are involved in the pathophysiologic mechanisms. DOI: http://dx.doi.org/10.3329/bmj.v41i2.18813 Bangladesh Medical Journal 2012 Vol. 41 No. 2: 61-63